Symptom interval of osteosarcoma around the knee joint: an analysis of 82 patients of a single institute. (15th November 2015) - Li, H.; Zheng, S.; Yu, W.; Huang, W.; Yao, Y.; Shen, Z.; Sun, Y.
Abstract : The time from first onset of symptoms or signs to a definitive diagnosis and initiation of treatment is defined as symptom interval (SI), the impact of SI on prognosis of patient with osteosarcoma (OS) remains unclear. A total medical records of 52 male and 30 female aged between 8 and 61 (median, 17) with OS around the knee joint were reviewed. Two components of SI, patient delay and professional delay were analysed. The median total SI was 2 months (range from 0.2 to 13.2 months). The median patient delay was 1.05 months (range from 0 to 12.5), and median professional delay was 0.45 months. Total SI and patient delay were not significantly different when patients were grouped by gender, age, tumour size and response to chemotherapy. Younger patients (<18 years) had shorter professional delay than older patients (≥18 years) ( P  =   0.02). Although there was a trend for longer time to lung metastasis in patients of SI <3 months, there was no significant difference compared with patients of SI ≥3 months ( P  =   0.15). In this study, younger patients had shorter professional delay than older patients. There was no significant correlation between SI and time to lung metastasis.